Assessment of disposal practices of expired and unused medications among community pharmacies in Anambra State southeast Nigeria: a mixed study design - Iweh Michael; Brian Ogbonna; Nduka Sunday; Maureen Anetoh; Okonta Matthew (Taylor & Francis Group, 2019)
Background Expired or unused medicines are potentially toxic substances that should be managed effectively to avoid accumulation of potentially toxic pharmaceuticals in the environment. In Nigeria, there is currently limited literature on the methods and protocols used by community pharmacists in the disposal of expired drugs. This study assessed disposal practices of expired and unused medications by pharmacists in Anambra State and compared them to the National Agency for Food and Drug Administration and Control (NAFDAC) guideline on disposal of expired drugs. Methods A questionnaire survey and key informant interview (KII) was used for the study. The pre-tested revised and adapted questionnaires were sent to all the 103 community pharmacies in Pharmacists Council of Nigeria (PCN) 2015 record of registered pharmacies in Anambra State. The participants were asked questions about how they disposed of expired and unused medications. The respondents that used NAFDAC or drug wholesalers were asked questions on how the third party destroys their expired drugs. In addition to the use of a questionnaire, KII was conducted to assess relevant professionals and stakeholders in this area. Results The study recorded 77 successfully returned questionnaires out of the 103 distributed and a response rate of 74.8%. The various disposal methods were: through NAFDAC 28.0 (31.8%), drug distributors 21.0 (23.9%), rubbish bins 8.0 (9.1%); this was mainly for solid dosage forms. However, 6.0(7.1%) reported that they used the sink to dispose of their liquid dosage forms and 24.0 (29.6%) noted they do not stock Class B controlled drugs. A lesser proportion of respondents 18.0 (23.4%) complied fully with the national guideline on disposal of expired drugs, while 17.0 (22.1%) complied partially and 42.0 (54.5%) did not comply. Some of the respondents 17.0 (22.1%) reported that NAFDAC uses incineration or other forms of heat to dispose of expired drugs, but 19.0 (24.7%) reported they do not know how NAFDAC dispose of their expired drugs. Majority of the respondents 55.0 (71.4%) suggested the state-run disposal system. Conclusion Poor compliance with the national guideline for medication disposal increases the potential risk of contamination of our environment and increases the possibility of ingesting toxic pharmaceutical wastes by humans and animals. This underscores the need for improvement on expired drugs management protocols to prevent contaminations and the attendant health hazards.